2020
DOI: 10.3389/fimmu.2020.00215
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus S-Layer-Mediated Innate Interactions During Endophthalmitis

Abstract: Bacillus endophthalmitis is a severe intraocular infection. Hallmarks of Bacillus endophthalmitis include robust inflammation and rapid loss of vision. We reported that the absence of Bacillus surface layer protein (SLP) significantly blunted endophthalmitis severity. Here, we further investigated SLP in the context of Bacillus-retinal cell interactions and innate immune pathways to explore the mechanisms by which SLP contributes to intraocular inflammation. We compared phenotypes of Wild-type (WT) and SLP def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 140 publications
(245 reference statements)
1
40
0
Order By: Relevance
“…The mechanism for this effect was linked to activation of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and subsequent inflammatory mediator production from Muller cells [17]. Further investigation revealed that SlpA activated both TLR2 and TLR4 in vitro, and that administration of TLR2/4 inhibitors attenuated the severity of infection in our mouse model (18,24). These results…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…The mechanism for this effect was linked to activation of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and subsequent inflammatory mediator production from Muller cells [17]. Further investigation revealed that SlpA activated both TLR2 and TLR4 in vitro, and that administration of TLR2/4 inhibitors attenuated the severity of infection in our mouse model (18,24). These results…”
Section: Discussionsupporting
confidence: 53%
“…At 4 hours postinfection with a CerO-deficient B. cereus strain, TLR4dependent inflammatory mediators were significantly downregulated [33]. TLR4 contributed to the inflammatory response to B. cereus [22], and was activated by purified B. cereus SlpA protein [18]. In addition to direct cellular cytotoxicity, CerO as a CDC might interact with and/or activate TLR4 [34][35][36][37], inciting inflammation during B. cereus endophthalmitis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations